The Association between Academic-Induced Stress with An Incident of Dyspepsia on Grade XII Natural Science Majors at 81 Senior High School East Jakarta in 2019 - Tamimi, Lamya Hisyam; Herardi, Ryan; Wahyuningsih, Sri (Jurnal Penyakit Dalam Indonesia, 2020)
Introduction. Dyspepsia is a group of symptoms that are assumed to have it’s source from the upper digestive tract. However, one of the main causes of dyspepsia in adolescent is psychosocial, including stress. Stress in adolescent are commonly academic-induced. This study was aimed to observe the association between the level of academic-induced stress with an incident of dyspepsia, particularly of students who are in grade XII and major in natural sciences. Methods. This cross sectional study was conducted at 81 Senior High School East Jakarta using educational stress scale for adolescents (ESSA) questionnaire dan Short form-Leeds to dyspepsia questionnare (SF-LDQ). It also uses total sampling technique where 88 respondents have participated and then sampled. Bivariate analysis was performed by Chi-square test using the SPSS program. Results. The respondents were 88 students consisted of 41 (46.6%) boys, 47 (53.4%) girls, and were dominated by 17-year-old students (77.3%). Almost all respondents experience mid-to-high level of academic stress that around 64 students (72.7%) and dominated by girls and age 17. It is also shown that around 51 students (58%) have experienced dyspepsia and dominated by girl and age 17. This study also shown that the symptoms that were considered as the most disturbing by respondents that are suffering from dyspepsia were nausea that around 21 (41.2%), followed by indigestion that around 18 (35.3%). The result of bivariate analysis shows that there was a significant association between the level of academic-induced stress with an incident of dyspepsia (p<0.001; OR=7.1 [CI 95% 2.44-20.68]). Conclusion. There is apparently a significant association between academic-induced stress with an incident of dyspepsia on grade XII natural science majors at 81 Senior High School East Jakarta in 2019